Metal Halide Perovskites for High‐Energy Radiation Detection. Issue 22 (11th October 2020) - Kakavelakis, George; Gedda, Murali; Panagiotopoulos, Apostolis; Kymakis, Emmanuel; Anthopoulos, Thomas D.; Petridis, Konstantinos
Abstract: Metal halide perovskites (MHPs) have emerged as a frontrunner semiconductor technology for application in third generation photovoltaics while simultaneously making significant strides in other areas of optoelectronics. Photodetectors are one of the latest additions in an expanding list of applications of this fascinating family of materials. The extensive range of possible inorganic and hybrid perovskites coupled with their processing versatility and ability to convert external stimuli into easily measurable optical/electrical signals makes them an auspicious sensing element even for the high‐energy domain of the electromagnetic spectrum. Key to this is the ability of MHPs to accommodate heavy elements while being able to form large, high‐quality crystals and polycrystalline layers, making them one of the most promising emerging X‐ray and γ ‐ray detector technologies. Here, the fundamental principles of high‐energy radiation detection are reviewed with emphasis on recent progress in the emerging and fascinating field of metal halide perovskite‐based X‐ray and γ ‐ray detectors. The review starts with a discussion of the basic principles of high‐energy radiation detection with focus on key performance metrics followed by a comprehensive summary of the recent progress in the field of perovskite‐based detectors. The article concludes with a discussion of the remaining challenges and future perspectives. Abstract : Metal halide perovskites have emerged as a promising family of electronic materials for application in optoelectronics. One area where scientific interest in these materials has been intensifying is high‐energy radiation detection. This review discusses the progress in the application of metal halide perovskites for direct & indirect X‐ray and Gamma‐ray detection.